The critical discourse analysis on pornography news of “V Garut” at TribunJabar.id online media - Nurhadi, Zikri Fachrul; Marlina, Neneng Cucu; Firdaus, Mochamad (Penerbit Universiti Kebangsaan Malaysia, 2020)
The emergence of pornography cases that had gone viral on social media with the tagline "V Garut" shocked the public because the act was committed by a woman and several men. The female suspect claimed that this act was done because of coercion and pressure that the male suspect had put on her. The research aims to explain the level of text, social cognition and social context of the pornography news of "V Garut" on the online media of TribunJabar.id. The research used a qualitative descriptive method with the theoretical approach of critical discourse analysis by Teun A. Van Dijk. Data collection techniques used observation, interviews, and documentation. The research object was related to the news of "V Garut" on the online media TribunJabar.id with two informants. The results of research at the text level in the elements of macrostructures, superstructures and microstructures explain the existence of a discourse indicating an unfavourable situation such as violence and marginalization on the role of "V Garut". Journalists’ social cognition tends to judge this case as “unique” phenomenon, not focusing on a social issue that must be addressed in society. Based on the analysis of the social context of this news, it can be seen that there is a powerful practice of the media and the authority’s access in reporting the “V Garut” case.